A bivalent pneumococcal histidine triad protein D-choline-binding protein A vaccine elicits functional antibodies that passively protect mice from Streptococcus pneumoniae challenge. Issue 11 (1st November 2016) - Ochs, Martina M.; Williams, Kimberley; Sheung, Anthony; Lheritier, Philippe; Visan, Lucian; Rouleau, Nicolas; Proust, Emilie; de Montfort, Aymeric; Tang, Mei; Mari, Karine; Hopfer, Robert; Gallichan, Scott; et al.
ABSTRACT: Vaccines based on conserved pneumococcal proteins are being investigated because serotype coverage by pneumococcal polysaccharide and polysaccharide conjugate vaccines is incomplete and may eventually decrease due to serotype replacement. Here, we examined the functionality of human antibodies induced by a candidate bivalent choline-binding protein A- pneumococcal histidine triad protein D (PcpA-PhtD) vaccine. Pre- and post-immune sera from subjects who had been vaccinated with the PcpA-PhtD candidate vaccine were tested in an established passive protection model in which mice were challenged by intravenous injection with Streptococcus pneumoniae serotype 3 strain A66.1. Serum antibody concentrations were determined by enzyme-linked immunosorbent assay (ELISA). Bacterial surface binding by serum antibodies was determined by a flow cytometry-based assay. Sera from 20 subjects were selected based on low activity of pre-immune samples in the passive protection model. Bacterial surface binding correlated more strongly with anti-PcpA (0.87; p < 0.0001) than with anti-PhtD (0.71; p < 0.0001). The odds ratio for predicting survival in the passive protection assay was higher for the anti-PcpA concentration (470 [95% confidence interval (CI), 46.8 to >999.9]) than for the anti-PhtD concentration (3.4 [95% CI, 1.9 to 5.6]) or bacterial surface binding (9.4 [95% CI, 3.6 to 24.3]). Pooled post-immune serum also protected mice against a challenge with S. pneumoniae serotype 3 strain WU2. Both anti-PcpA and anti-PhtD antibodies induced by the bivalent candidate vaccine mediate protection against S. pneumoniae . The results also showed that the ELISA titer might be useful as a surrogate for estimating the functional activity of antibodies induced by pneumococcal protein vaccines.